The Analysis of Student’s Mathematical Problem Solving Skills on the Topics of Square and Rectangle in Elementary School - Manik, Elisabeth; Herman, Tatang; Anjani, Cusni (International Conference on Elementary Education, 2024)
Mathematics learning has five aspects of mathematical proficiency that every student must have. These five aspects of mathematical proficiency are not abilities that students already have naturally, but are a combination of knowledge, skills, abilities and beliefs that students have and are obtained with the help of teachers through the learning process. One of the abilities that students must have is problem solving ability. Mathematics lessons that are closely related to everyday life are square and rectangle. The purpose of this study is to see how students’ problem solving skills on the topics of square and rectangle in elementary school. This research uses the Systematic Literatul Review (SLR) method or literature review. Data collection in this study was carried out by collecting relevant articles related to students’ problem solving skills in square and rectangle materials. The results of this study indicate that students’ problem solving skills on the topics of square and rectangle still need to be improved. This statement is supported by various theories and research on how students’ problem solving skills on square and rectangle materials.